22. EVALUATION OF THE RESULTS OF CARE OF PATIENTS WITH COMPLICATED ANAL FISTAKE WOUNDS IN THE JOURNAL OF GENERAL SURGERY, TRANSPORTATION HOSPITAL, 2024 (Vietnam Journal of Community Medicine, 2026)
This descriptive case series included three adult men with recurrent complex fistula-in-ano managed in the Department of General Surgery, Transport Hospital. Preoperative pelvic MRI mapped fistula tracts; sphincter-preserving surgery (selective fistulotomy and staged seton for horseshoe tracts) was performed, followed by standardized ERAS-based postoperative care. Early outcomes were favorable with a hospital stay of approximately 7–8 days, no fecal incontinence, and no early recurrence at 1-month follow-up; wounds healed satisfactorily. MRI-guided, sphincter-sparing surgery combined with ERAS appears feasible and effective in the short term; larger cohorts with longer follow-up are warranted.